2000
DOI: 10.1093/treephys/20.11.761
|View full text |Cite
|
Sign up to set email alerts
|

Regional assessment of boreal forest productivity using an ecological process model and remote sensing parameter maps

Abstract: An ecological process model (BIOME-BGC) was used to assess boreal forest regional net primary production (NPP) and response to short-term, year-to-year weather fluctuations based on spatially explicit, land cover and biomass maps derived by radar remote sensing, as well as soil, terrain and daily weather information. Simulations were conducted at a 30-m spatial resolution, over a 1205 km(2) portion of the BOREAS Southern Study Area of central Saskatchewan, Canada, over a 3-year period (1994-1996). Simulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 36 publications
1
47
0
1
Order By: Relevance
“…For example, the duration of the non-snow season and the timing of the spring melt has a great impact on the surface energy balance and on plant productivity in the Arctic. For a similarly regionthe boreal forest in Canada - Kimball et al (2000) found a relationship between the date of first thaw and biomass production. They have shown a decrease of net primary production by 9-17% for 10-day delay in spring thaw.…”
Section: Climate Change Signalmentioning
confidence: 94%
“…For example, the duration of the non-snow season and the timing of the spring melt has a great impact on the surface energy balance and on plant productivity in the Arctic. For a similarly regionthe boreal forest in Canada - Kimball et al (2000) found a relationship between the date of first thaw and biomass production. They have shown a decrease of net primary production by 9-17% for 10-day delay in spring thaw.…”
Section: Climate Change Signalmentioning
confidence: 94%
“…The process model employed for scaling GPP was the Biome-BGC model (Kimball, Keyser, Running, & Saatchi, 2000;Kimball, Running, & Saatchi, 1999;Kimball, Thornton, White, & Running, 1997;Running, 1994;Running & Hunt, 1993). A version similar to that used in this study has been applied and tested in temperate (Coops, Waring, Brown, & Running, 2001;Running, 1994) and boreal (Kimball et al, 1997(Kimball et al, , 1999 forests.…”
Section: Process Model Applicationmentioning
confidence: 99%
“…Less than 20% of the days at either site required filling in missing data with measurements from elsewhere. The effectiveness of the model itself has been documented to some degree with regard to NPP in boreal (Kimball et al, 2000(Kimball et al, , 1999(Kimball et al, , 1997 and temperate (Running, 1994) forests. The used of binned GPP data at the tower makes it difficult to closely evaluate the effectiveness of modeled GPP responses to day-to-day variation in meteorology but the model output is clearly tracking most of the oscillations during the growing season.…”
Section: Assessment Of Bigfoot Gpp Productsmentioning
confidence: 99%
“…Various methods such as process models and remote sensing-based approaches have been developed and used [4][5][6][7]. The process models-based methods do not generate spatially explicit predictions and often lead to a large amount of uncertainty for specific sites, partly because too many variables and input parameters are required to run the models and partly because different source data such as climate and soil data have very coarse spatial resolutions [8][9][10]. In contrast, remote sensing-based approaches have become popular due to their unique characteristics in data collection and presentation; that is, multitemporal remote sensing images not only reveal spatial variability, spatial distributions, and patterns of forests but also provide the potential to estimate their changes over time [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%